2015
DOI: 10.2174/2210289201506010018
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Phosphide-induced Hepato-nephrotoxicity and Oxidative Damage in Rats: The Protective Effect of α-lipoic Acid

Abstract: The present experiment was carried out to investigate the effectivness of -lipoic acid in allevating the toxicity of aluminium phosphide on biochemical parameters, free radicals and enzyme activities in plasma, liver and kidney of male rats. Animals were orally treated with aluminium phosphide, -lipoic acid and their combination for 30 consecutive days. Treatment with aluminium phosphide led to significant decrease in plasma total protein and glucose and increase in transaminases, phosphatases, urea, creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Therefore, increased FBS in our study is possibly associated with reduced leptin levels. Our result is in agreement with several studies on persistent organic pollutants (POPs) including Phthalate Esters and BPA [32,33] and is in contrast with the findings of Yousef et al that showed decrease in glucose level of rats treated with aluminium phosphide [34].…”
Section: Effect On Biochemical Parameterssupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, increased FBS in our study is possibly associated with reduced leptin levels. Our result is in agreement with several studies on persistent organic pollutants (POPs) including Phthalate Esters and BPA [32,33] and is in contrast with the findings of Yousef et al that showed decrease in glucose level of rats treated with aluminium phosphide [34].…”
Section: Effect On Biochemical Parameterssupporting
confidence: 93%
“…Furthermore, they confirmed that ALP treatment significantly reduces GSH (glutathione), GST (glutathione S-transferase), and CAT (catalase) in plasma. Also, α-lipoic acid combined with ALP could decrease the toxic effects in major parameters [29].…”
Section: Effect On Histopathological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were randomly separated into 6 groups (10 rats each): control group: received 0.2 ml of distilled water/ 100 g bwt/ day orally (vehicle of TAA and ALA) using a stomach tube three times a week, TAA-treated group: received intraperitoneal (IP) injection of TAA (250 mg/kg bwt dissolved in distilled water) three times a week according to Abdou et al (2015). ALA-treated group: received ALA (100 mg/kg bwt/day) orally using a stomach tube three times a week according to Yousef et al, (2015). SIL-treated group: received SIL (100 mg/kg bwt/day) orally three times a week according to ElSenosiy et al (2015).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Aluminium phosphide (ALP) is a fumigant pesticide that is used in the preservation of agricultural products and processed foods. 1 It has gained extensive use worldwide due to its low cost, efficacy, short half-life and low toxicity of its decomposition products. 2 However, it has proven to be highly toxic to both humans and animals on exposure.…”
Section: Introductionmentioning
confidence: 99%